2017
DOI: 10.1371/journal.pone.0179287
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing practitioner adoption of carer-led assessment in palliative homecare: A qualitative study of the use of the Carer Support Needs Assessment Tool (CSNAT)

Abstract: IntroductionInformal caregivers play a pivotal role in supporting patients approaching the end of life. The Carer Support Needs Assessment Tool (CSNAT) is designed to facilitate person-centred assessment and support through a process that is practitioner-facilitated, but carer-led. This study explored practitioners’ experiences of implementing the CSNAT in palliative homecare.MethodsWe conducted qualitative interviews/focus groups with 20 practitioners in one UK hospice homecare service (18 nurses, two healthc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Also, one study of informal caregivers to dementia care receivers showed that informal caregivers in Sweden spend less time in their caregiving when compared with caregivers in another European country, Italy (Chiatti et al, ). Systems for supporting informal caregivers are present in other European countries as well, such as the United Kingdom's Carer's Assessments for adult carers of people who are disabled, ill or elderly and the Carer Support Needs Assessment Tool (Austin, Ewing, & Grande, ). However, caregivers perform a variety of tasks that differ between families, which may complicate the policy‐making and design of a general intervention for this group.…”
Section: Discussionmentioning
confidence: 99%
“…Also, one study of informal caregivers to dementia care receivers showed that informal caregivers in Sweden spend less time in their caregiving when compared with caregivers in another European country, Italy (Chiatti et al, ). Systems for supporting informal caregivers are present in other European countries as well, such as the United Kingdom's Carer's Assessments for adult carers of people who are disabled, ill or elderly and the Carer Support Needs Assessment Tool (Austin, Ewing, & Grande, ). However, caregivers perform a variety of tasks that differ between families, which may complicate the policy‐making and design of a general intervention for this group.…”
Section: Discussionmentioning
confidence: 99%
“…While the hospice model emphasizes the delicate balance of the IC being both cared for by the hospice providers and a caregiver for the patient, 15 health-care professionals often struggle to recognize and applaud the expertise of the IC. 52,56 The Carers' Alert Thermometer (CAT) 57 and the Carer Support Needs Assessment Tool (CSNAT) 58 are important instruments that can make a significant impact in alleviating deficiencies in ICs' knowledge of services and caregiving skills and help to authenticate the ICs' important role as expert caregivers. Including ICs in interdisciplinary team meetings 34,59 is another possible way to ensure ICs have adequate knowledge of available resources, have their specific needs addressed, and feel like an equal part of the team.…”
Section: Discussionmentioning
confidence: 99%
“…However, many participants described methods of using the CSNAT that are inconsistent with the recommended approach, such as, using the CSNAT as an 'add-on' to existing nurse-led practice, and not revisiting the CSNAT. Austin et al (2017) also found that the CSNAT was used as an 'add on' to existing practice in their study of its use in palliative home care. This may have been because practitioners did not fully appreciate that CSNAT implementation requires a shift in their carer support approach from being practitioner-led, to practitioner-facilitated but carer-led assessment.…”
Section: The Csnat Approachmentioning
confidence: 99%